Environmental Impact Assessment: Implications of Bridge Construction Venture in Bangladesh (Journal of Environmental Science and Natural Resources, 2022)
This study was conducted to assess the environmental impacts of the proposed Kashil Bridge over the river Jhinai at Basail upazila of Tangail district in Bangladesh during January to September 2019. The environmental impact assessment (EIA) is a mandatory process to assess the environmental consequences of an existing or proposed project and to delineate any environmental management measures that must be integrated into the plan to ensure that the project is technically, economically, socially and environmentally acceptable. The EIA preparation led to the identification of potential environmental and social impacts due to proposed bridge pre-construction, construction and operation activities on the Jhinai River and feasible remedial measures as included in the Environmental Management Plan (EMP). A field mobilization was conducted in project area to find out the environmental baseline (surface water, groundwater, soil, sediments, air, noise and ecology) information and identification of possible impacts. The focused group discussions (FGDs), questionnaire survey (QS) and key informants interview (KII) were conducted to collect relevant information. Secondary data were collected from Local Government Engineering Department, Upazila Agriculture Office, Upazila Fisheries Office, Department of Environment (DoE) and published relevant articles. Analyzing overall impacts, EIA study found that these possible negative impacts are considerable if some mitigation measures are applied. This new bridge will not only increase the communication facilities but also increase the economic flow together with other facilities. Finally, the EIA study suggested some defined EMP which will help to minimize the probable adverse impacts of the bridge construction site over the Jhinai River.Environ. Sci. & Natural Resources, 13(1&2): 13-18, 2020